Improving the Quality of Life for the Elderly Through the GALASEMA Application - Pepin Nahariani; Shanti Rosmaharani; Iin Noviana (Babali Publisher, 2023)
The elderly are a group that has a high risk of experiencing a decline in health status so that it will affect the quality of life. One alternative solution that involves technological sophistication is the GALASEMA (Healthy and Independent Elderly Movement) application, which functions to improve the health status of the elderly. The purpose of the study was to determine the improvement of the quality of life of the elderly through the GALASEMA application. The design of this study used a pre-experimental one-group pre-post test design. The population in this study amounted to 345 elderly. The sample in this study amounted to 100 elderly. The sampling technique used in this research is simple random sampling technique. The questionnaire used was WHOQOL-BREF to assess quality of life. Data processing using Wilcoxson statistical test. The results of the statistical test p value 0.00 <0.05, which means the application can improve the quality of life of the elderly. it is hoped that the elderly can access this application and can be used at home independently with the family.